2015
DOI: 10.1186/s13036-015-0015-y
|View full text |Cite
|
Sign up to set email alerts
|

Collective cell migration of smooth muscle and endothelial cells: impact of injury versus non-injury stimuli

Abstract: BackgroundCell migration is a vital process for growth and repair. In vitro migration assays, utilized to study cell migration, often rely on physical scraping of a cell monolayer to induce cell migration. The physical act of scrape injury results in numerous factors stimulating cell migration – some injury-related, some solely due to gap creation and loss of contact inhibition. Eliminating the effects of cell injury would be useful to examine the relative contribution of injury versus other mechanisms to cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…It was reported that smooth muscle cells migrated faster on the gelatin-coated surface than on the uncoated polystyrene surface [33]. An increase of 63% in the migration rate from 24 to 48 h was observed in a barrier wound-healing assay [33]. Under the same conditions, for human umbilical vein endothelial cells, the migration rate was even six times faster on the gelatin-coated surface than on the uncoated polystyrene one [33].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that smooth muscle cells migrated faster on the gelatin-coated surface than on the uncoated polystyrene surface [33]. An increase of 63% in the migration rate from 24 to 48 h was observed in a barrier wound-healing assay [33]. Under the same conditions, for human umbilical vein endothelial cells, the migration rate was even six times faster on the gelatin-coated surface than on the uncoated polystyrene one [33].…”
Section: Resultsmentioning
confidence: 99%
“…Gelatin, an irreversibly hydrolyzed form of collagen, is widely used as a coating material in cell culture for improving cell attachment [32]. It was reported that smooth muscle cells migrated faster on the gelatin-coated surface than on the uncoated polystyrene surface [33]. An increase of 63% in the migration rate from 24 to 48 h was observed in a barrier wound-healing assay [33].…”
Section: Resultsmentioning
confidence: 99%
“…4). While the injury free release of contact inhibition is sufficient to induce cell migration in cell exclusion assays 2,6,9,14 , the injury inflicted upon the cells in scratch wound healing models with the associated disruption of cell adhesions and release of intracellular contents and signalling molecules has been shown to alter the microenvironment in the cell culture and to provide a critical input required for cell-cell coordination in the spreading of the wounded monolayer 1,3,4,6,7,9 . Thus, while cell exclusion assays provide repeatability and geometric control, they fail to induce an injury and the insert used in this study correspondingly led to slower gap closure kinetics compared to the three assays that inflicted injury upon the cell layer.
Figure 4Definition of regions of interest (ROI) along the scratch margins.
…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently serial high-resolution images are captured and analysed to quantify the dynamics of cell migration into the gap 3 . However, as the scratch is most commonly created manually using a pipette tip, the extent of the cellular injury and the geometry of the scratch is influenced not only by the scraping tool utilized, but also the level of manual control, the pressure exerted, the angle of the instrument and the velocity of scraping 3,4,6,7 . As a result, repeatability and reproducibility of the assays is limited and dependent on the manual dexterity of the researchers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation